IMPLEMENTASI FATWA DSN-MUI NO. 108/DSN-MUI/X/2016 TENTANG PEDOMAN PENYELENGGARAAN PARIWISATA BERDASARKAN PRINSIP SYARIAH PADA DESTINASI WISATA TALAO PAUH KOTA PARIAMAN - Fina Marliza Putri; Dewi Manda Angraini (ADISAM PUBLISHER, 2025)
This research was carried out at the Talao Pauh Tourism Destination which is one of the tourist destinations in Pariaman City which strives to become a leading tourist destination at the national and international level as stated in the vision of Pariaman City, namely Pariaman City of Tourism, Trade, Religious and Cultural Services. . The aim of this research is to determine the implementation of DSN-MUI fatwa no. 108/DSN-MUI/X/2016 at the Talao Pauh Tourist Destination, Pariaman City. The method used in this research is a qualitative method with a qualitative descriptive approach. Data collection was carried out by observation, interviews and documentation. Based on this research, it can be concluded that the Talao Pauh Tourist Destination has partially implemented sharia principles, including the existence of places of worship, namely prayer rooms, ablution places that are separated for men and women, the existence of a choice of tourist attractions that do not lead to pornography and idolatry such as playgrounds. family, water rides, tracking tourist bridges, the food provided at this tourist destination is also local culinary delights that are definitely halal. However, there are still aspects that need to be considered, namely the lack of supervision of visiting tourists, such as being a means for couples who are not yet legal husband and wife and are not in accordance with the DSN-MUI Fatwa because tourist destinations must be protected from immorality and adultery. Then, maintenance of public toilet facilities and improving cleanliness around tourist areas need to be considered to ensure compliance with the DSN-MUI fatwa that tourist destinations must maintain cleanliness, natural sustainability, sanitation and the environment.